Gut Microbiome and Neuroinflammation in Hypertension. Issue 3 (4th February 2022) - Richards, Elaine M.; Li, Jing; Stevens, Bruce R.; Pepine, Carl J.; Raizada, Mohan K.
Abstract : Hypertension is a worldwide problem with major impacts on health including morbidity and mortality, as well as consumption of health care resources. Nearly 50% of American adults have high blood pressure, and this rate is rising. Even with multiple antihypertensive drugs and aggressive lifestyle modifications, blood pressure is inadequately controlled in about 1 of 5 hypertensive individuals. This review highlights a hypothesis for hypertension that suggests alternative mechanisms for blood pressure elevation and maintenance. A better understanding of these mechanisms could open avenues for more successful treatments. The hypothesis accounts for recent understandings of the involvement of gut physiology, gut microbiota, and neuroinflammation in hypertension. It includes bidirectional communication between gut microbiota and gut epithelium in the gut-brain axis that is involved in regulation of autonomic nervous system activity and blood pressure control. Dysfunction of this gut-brain axis, including dysbiosis of gut microbiota, gut epithelial dysfunction, and deranged input to the brain, contributes to hypertension via inflammatory mediators, metabolites, bacteria in the circulation, afferent information alterations, etc resulting in neuroinflammation and unbalanced autonomic nervous system activity that elevates blood pressure. This in turn negatively affects gut function and its microbiota exacerbating the problem. We focus this review on the gut-brain axis hypothesis for hypertension and possible contribution to racial disparities in hypertension. A novel idea, that immunoglobulin A-coated bacteria originating in the gut with access to the brain could be involved in hypertension, is raised. Finally, minocycline, with its anti-inflammatory and antimicrobial properties, is evaluated as a potential antihypertensive drug acting on this axis.